Analisis Kualitas Pengungkapan Islamic Corporate Social Responsibility Bank Umum Syariah di Indonesia - Dian Yuni Anggraini; Rayna Kartika (Universitas Andalas, 2019)
This study aims to examine the quality of Islamic Corporate Social Responsibility (ICSR) disclosure in Indonesian Islamic Banks for 2014-2017. Content analysis was used to identify the quality of information disclosed. The observation of the study isusing 50 observations(13 Islamic Banks and for 4 years). The operational definition of ICSR is encompassed by Islamic economic responsibility, Islamic legal responsibility, Islamic ethical responsibility, and Islamic philanthropic responsibility. The study shows that the information disclosed is more dominated by quantitative than qualitative information. There are positive trend on ICSR disclosure. Therefore, the increasing disclosure trends can be considered as a first step toward improved Indonesian Islamic Banks’ ICSR disclosure. The increasing disclosure trends can be considered as the fact that Islamic Banks in Indonesia have increasing their interest in social problems. This study provides a valuable contribution to researchers and practitioners, as it extends the understanding of how the narrative disclosures on ICSR were produced by Indonesian Islamic Banks.